2008
DOI: 10.1016/j.ejvs.2008.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Traditional versus Endoscopic Saphenous Vein Stripping: A Prospective Randomized Pilot Trial

Abstract: The results of this study suggest that endoscopic GSV excision showed no difference in adverse events between treatments, although our pilot study may have been under-powered to demonstrate this. The SF-36 assessment suggests more rapid return to normal activities post-operatively in the endoscopic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Mean time needed to return to normal activity was 3.2 with SD 4 in patients underwent conventional surgery while it was 3.2 with SD 4.3 in patients group who underwent laser ablation. Assadian et al [26] also showed that, there was no significant difference between both groups regarding the ambulation time with slight privilege in the laser ablation group.…”
Section: Discussionmentioning
confidence: 93%
“…Mean time needed to return to normal activity was 3.2 with SD 4 in patients underwent conventional surgery while it was 3.2 with SD 4.3 in patients group who underwent laser ablation. Assadian et al [26] also showed that, there was no significant difference between both groups regarding the ambulation time with slight privilege in the laser ablation group.…”
Section: Discussionmentioning
confidence: 93%